A direct comparison of the effectiveness of two anti‐predator strategies under field conditions. (28th August 2013) - Carroll, J.; Sherratt, T. N.
Abstract Aposematism and crypsis are two widespread defensive strategies that have evolved in organisms to reduce attacks by predators. However, although both have been studied extensively, predation rates on unpalatable conspicuous prey have seldom been directly compared to those on palatable cryptic prey, and never in the field. In this study, we use established methods to compare the effectiveness of both defensive traits, by presenting artificial prey targets on trees where they were subject to attack by wild avian predators in a natural field setting. When partially consumed prey and those that had been completely removed were both treated as attacked by predators, there were no differences in attack rates between targets with the two defensive strategies. However, aposematic prey were completely consumed less often than cryptic prey, and partially consumed more often. This suggests that predators engage in taste rejection of unpalatable prey and/or feed on conspicuous prey more cautiously ('go‐slow' predation). We also observed significant differences in predation among experimental sites, in spite of their similarity and relatively close proximity, and among trials, which suggests that prey may experience highly variable predation in the wild. If aposematic prey are capable of surviving attacks by predators, then this represents a potential defensive benefit of aposematism over crypsis.